Implementasi Game Edukasi Berbasis Android Dalam Pembelajaran Alat Musik Tradisional Jawa Barat - Suprapti, Tati; Apriliani, Yuni (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Indonesia is a country that is rich in culture, one of the famous ones from Indonesia is its traditional musikal instruments, especially the West Java area which has many musikal instruments called waditra. Waditra is a term for sound instruments commonly used as traditional musikal instruments. Limitations occur because of the impossibility of teaching staff to directly show some musikal instruments from West Java in the learning process of Cultural Arts in recognizing musikal instruments. By utilizing the provision of applications that contain elements of education, it gives birth to new ways in one's learning process. From the problems that occur, to overcome them by making an educational game in introducing musikal instruments from the regions in Indonesia. By introducing the identity of each of these musikal instruments, it is able to provide insight to the children of SD Negeri Cidenok, Majalengka Regency. Based on the ADDIE development method (Analysis, Design, Development, Implementation, Evaluation), able to make educational games that are useful for learning media systematically for children at SD Negeri Cidenok, Majalengka Regency. The results obtained from blackbox testing, which is to test the functions in the game so that it runs well. In this trial, it was found that every game scene functions and runs properly so that this research is said to be successful because the game is worthy of being used as an innovative and creative learning medium and helps children in understanding local musikal instruments.